2008
DOI: 10.1186/1749-7922-3-31
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of perforation peritonitis in Pakistan: 300 cases Eastern experience

Abstract: Background: Perforation peritonitis is the most common surgical emergency encountered by the surgeons all over the world as well in Pakistan. The spectrum of etiology of perforation peritonitis in tropical countries continues to differ from its western counter part. This study was conducted at Dow University of health sciences and Civil Hospital Karachi (DUHS & CHK) Pakistan, designed to highlight the spectrum of perforation peritonitis in the East and to improve its outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
72
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 26 publications
(21 reference statements)
18
72
3
Order By: Relevance
“…We found that surgery within the first six hour after diagnosis of perforation peritonitis had good outcomes in relations of earlier resumption of normal diet , shortening the length of stay in hospital and length of stay in ICU. Our overall mortality rate was 10%, which is lower [4][5][6][7] than reported by other studies. In comparision to early intervention patients, late intervention patients develop more postoperative complications (34.3 % vs. 17.8%, P=0.022).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…We found that surgery within the first six hour after diagnosis of perforation peritonitis had good outcomes in relations of earlier resumption of normal diet , shortening the length of stay in hospital and length of stay in ICU. Our overall mortality rate was 10%, which is lower [4][5][6][7] than reported by other studies. In comparision to early intervention patients, late intervention patients develop more postoperative complications (34.3 % vs. 17.8%, P=0.022).…”
Section: Discussioncontrasting
confidence: 76%
“…We did not find any significant difference between the two groups in respect to causes of perforation and site of perforation (P<0.05) as shown in Table 3. Table 2.Clinical parameters Table 3.Etiology and site of perforation peritonitis Median time to intervention was 2.85 h (range 2-5) and 7.23 h (range [6][7][8][9][10][11][12][13][14][15][16][17][18], in the two groups respectively.Overall postoperative complication was detected in 56 patients (28%). Wound infection (33% in Group I vs. 36% in Group II) was most common complications followed by dyselectrolytaemia (23% vs. 22%).…”
Section: Methodsmentioning
confidence: 99%
“…Our study showed 58.48% patient had perforations due to peptic disease which was the most common cause of perforation. This was more than studies done by Jhobtaet al 7 , Afridi et al 8 and Yadav et al 6 .…”
Section: Discussionmentioning
confidence: 62%
“…Mean age in our study was 30 which was comparable to that Yadav et al 6 , who reported the mean age to be 33.9 yrs. Males were seen to predominate in incidence in all the studies [6][7][8] . The highest male preponderance was noticed by Jhobtaet al 7 , where the ratio of male to female was 5.2:1, followed by Yadav et al6 where the ratio was 4.9:1, which was almost similar to our study in which the ratio was 5.6:1.…”
Section: Discussionmentioning
confidence: 99%
“…2 Duodenal perforation secondary to ulcer was the most common perforation noticed in our study as supported by other studies in past. 11,12 Causative factors also show a wide geographical variation. According to a study from India, infections formed the most common cause of perforation peritonitis, 10 around 50% cases in this study were due to typhoid.…”
Section: Discussionmentioning
confidence: 99%